Conceptual Considerations for Device-Based Therapy in Acute Decompensated Heart Failure: DRI2P2S. (April 2020) - Rosenblum, Hannah; Kapur, Navin K.; Abraham, William T.; Udelson, James; Itkin, Maxim; Uriel, Nir; Voors, Adriaan A.; Burkhoff, Daniel
Abstract : Acute decompensated heart failure remains the most common cause of hospitalization in older adults, and studies of pharmacological therapies have yielded limited progress in improving outcomes for these patients. This has prompted the development of novel device–based interventions, classified mechanistically based on the way in which they intend to improve central hemodynamics, increase renal perfusion, remove salt and water from the body, and result in clinically meaningful degrees of decongestion. In this review, we provide an overview of the pathophysiology of acute decompensated heart failure, current management strategies, and failed pharmacological therapies. We provide an in depth description of seven investigational device classes designed to target one or more of the pathophysiologic derangements in acute decompensated heart failure, denoted by the acronym DRI2 P2 S. Dilators decrease central pressures by increasing venous capacitance through splanchnic nerve modulation. Removers remove excess fluid through peritoneal dialysis, aquaphoresis, or hemodialysis. Inotropes directly modulate the cardiac nerve plexus to enhance ventricular contractility. Interstitial devices enhance volume removal through lymphatic duct decompression. Pushers are novel descending aorta rotary pumps that directly increase renal artery pressure. Pullers reduce central venous pressures or renal venous pressures to increase renal perfusion. Selective intrarenal artery catheters facilitate direct delivery of short acting vasodilator therapy. We also discuss challenges posed in clinical trial design for these novel device–based strategies including optimal patient selection and appropriate end points to establish efficacy. Abstract : Supplemental Digital Content is available in the text.